KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PELAKSANAAN EVALUASI PEMBELAJARAN - Ali Miftakhu Rosyad (Institut Agama Islam Negeri (IAIN) Bone, 2019)
Islamic Education is an important part of the education system in Indonesia. The field study has important responsibilities in constructing the student character. In the learning process of Islamic Education the teachers must have good competence in the process of planning, implementing, and evaluating learning. To improve the learning evaluation system the first thing a teacher must do is improve the process first. Assessment in learning Islamic education must touch at least the cognitive, affective, and psychomotor aspects. Educational evaluation is also the domain of educational technology. The domain is certainly inseparable from other domains, namely design, development, use (utilization) and management (management). Therefore in determining an evaluation mechanism it is necessary to look at other domains so that learning outcomes can be generatedKeywords: teacher competence, Islamic education, learning evaluation